Desain Kontruksi Ijtihad Ushuliyah Imam Al-Syafi’i - ainol yaqin (Istinbath : Jurnal Hukum, 2020)
Imam ash-Syafi’i is the founder of ash-Syafi’i school (Shafi'iyah) as well as the first jewel layer of the science of ushul fiqh, as Aristotle laid the foundation of logic. Because he had contributed in composing a ushul fiqh logically, critically and systematically in his monumental work, ar-Risalah. This article focuses on reviewing the construction of ijtihad imam asy-Syafi’i with a concept analysis approach. According to him, the arguments and sources of Islamic law are based on; a) al-qur’an, as-sunnah, ijma`, and qiyas. While in al-Umm, he included qawl shahabah as one of the basis of Islamic law. The construction of ijtihad which he initiated has its own characteristics by combining manhaj ijtihad patterns ahlu al-ra'yi and ahlu al-hadith. The emergence of Imam al-Shafi’i ended a fierce polemic from followers of both faction. However, the legal products he designed do not contain absolute truth, because the results of ijtihad can be true and can also be wrong. He stated my opinion was correct but it could be wrong and the opinions of others were wrong but it could be true.